Me3Si−SiMe2[oCON(iPr)2−C6H4]: An Unsymmetrical Disilane Reagent for Regio‐ and Stereoselective Bis‐Silylation of Alkynes. (12th March 2018) - Xiao, Peihong; Cao, Yanjun; Gui, Yingying; Gao, Lu; Song, Zhenlei
Abstract: The air‐stable unsymmetrical disilane Me3 Si−SiMe2 [ o CON( i Pr)2 C6 H4 ] has been developed for bis‐silylation of alkynes. This reagent tolerates a range of functional groups, providing Z ‐vinyl disilanes in high yields. It is proposed that the phenyl‐ring‐tethered amide group directs oxidative addition of Pd 0 into the Si−Si bond, which might facilitate formation of a six‐membered Pd cycle, generating products with good to excellent regioselectivity. Abstract : Ein luftstabiles, unsymmetrisches Disilan, Me3 Si‐SiMe2 [ o CON( i Pr)2 C6 H4 ], wurde für die Bis‐Silylierung von Alkinen entwickelt. Es toleriert eine Reihe funktioneller Gruppen und liefert Z ‐Vinyldisilane in hohen Ausbeuten. Vermutlich steuert eine Amidgruppe am Phenylring die oxidative Addition von Pd 0 in die Si‐Si‐Bindung unter Bildung eines sechsgliedrigen Pd‐Cyclus. Die Produkte entstehen mit gutem bis exzellentem Regioisomerenverhältnis (r.r.).